Time as Capital: Exploring Time Management and Business Performance Among Traditional and Digital Marketplace Sellers in Uzbekistan - O'g'li, Evatov Elomon O'tkir; Askolani; Surachman, Eka (Integrasi Sains Media, 2025)
Time management is a critical determinant of business success, especially in fast-evolving marketplace environments. In Uzbekistan, where traditional bazaars coexist with emerging digital commerce platforms, sellers face unique challenges in balancing task prioritization, delegation, and responsiveness. This study examines how marketplace actors in Uzbekistan allocate their time across traditional, digital, and hybrid business environments. Anchored in the Eisenhower Matrix and Temporal Motivation Theory (TMT), the research employs a qualitative case study design involving semi-structured interviews with 15 marketplace sellers in Tashkent, Samarkand, and the surrounding regions. Findings reveal that digital sellers partially align with urgency-based prioritization due to platform notifications yet often neglect non-urgent strategic tasks. Traditional vendors are primarily reactive, focusing on repetitive, urgent routines at the expense of long-term growth. Across all categories, procrastination is a persistent issue, rooted not only in workflow gaps but also in cultural resistance to delegation and low engagement with digital planning tools. The study highlights how time management practices are deeply embedded in socio-cultural norms and infrastructural constraints. A conceptual model is proposed linking cultural attitudes, delegation behaviors, motivational responsiveness, and workflow structuring to time efficiency and operational performance. This model offers a foundation for future quantitative research and potential interventions tailored for hybrid marketplaces. The findings suggest the need for culturally adaptive time management strategies, mobile-integrated planning tools, and behavioral support systems to enhance marketplace productivity in Uzbekistan's digital economy.